ESP RESEARCH TRENDS IN ASIAN CONTEXT - Arpawan Jantaravipark; Amporn Sa-ngiamwibool (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2015)
Due to the influence of global and regional economic changes, English for Specific Purposes (ESP) plays a more vital role in English language studies worldwide, including in Asian context. A look at any issues relat-ing to Asian ESP will shed light to the needs of English in this content. This present study therefore sur-veyed recent trends of ESP research in this context, with the purpose of the study which aimed to explore recent trends in Asian ESP research from 2005 to 2013. The Asian ESP Journal which has been a flagship in this area was chosen for the content analysis in this study. The results revealed that the research trends in ESP were primarily based on qualitative research method. Future research study may explore international ESP to compare the results of the study with this one. Keywords: ESP, trends in research, Asian context